1987
DOI: 10.1016/0006-8993(87)90372-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory innervation of the external and internal genitalia of the female rat

Abstract: Using a whole-nerve recording method, the genitalia of the female rat were found to receive afferent innervation as follows. Pelvic nerve: vagina, cervix, and perineal skin; hypogastric nerve: cervix and proximal three fifths of the uterus; pudendal nerve: skin of perineum, inner thigh, and clitoral sheath. It is probable that the pudendal and pelvic nerves are activated during copulation, and that all 3 nerves are activated during parturition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…Sensory input arising from vaginocervical stimulation is mainly relayed via the pelvic nerve [17,30]. These fibers can be described as afferent parasympathetic directed at the L6-S1 segments of the spinal cord [45].…”
Section: Vaginocervical Stimulationmentioning
confidence: 99%
“…Sensory input arising from vaginocervical stimulation is mainly relayed via the pelvic nerve [17,30]. These fibers can be described as afferent parasympathetic directed at the L6-S1 segments of the spinal cord [45].…”
Section: Vaginocervical Stimulationmentioning
confidence: 99%
“…Electrical stimulation of the pelvic nerve elicited contractions in both cervix and uterus (41) and increased intravaginal pressure (35). Accordingly, recordings from the pelvic nerve activity showed that it responds to mechanical stimulation of the vagina and to stretching of the cervix during parturition (37). Pelvic neurectomy blocks induction of pseudopregnancy (10), presumably by blocking the PRL increase after mating (44).…”
Section: R679mentioning
confidence: 99%
“…In female rats, the internal genitalia are innervated primarily by the hypogastric nerves (sympathetic) and pelvic nerves (sympathetic and parasympathetic) that terminate peripherally in the pelvic or uterine cervical ganglia (37). Visceral afferent fibers of the pelvic nerve are more sensitive than hypogastric nerve fibers to uterine and cervical mechanostimulation (4).…”
Section: R679mentioning
confidence: 99%
“…Previous studies have focused on inflammation or distension of the uterus or vagina to understand mechanisms of chronic pain from these structures, or pressure applied to the vaginal surface of the uterine cervix, which induces antinociception and mating related behaviors in rodents (Berkley et al 1988;Komisaruk and Larsson 1971;Peters et al 1987;Wesselmann et al 1998). Because these are not necessarily relevant to pain produced by distension of the lower uterine segment and endocervix, we developed a model of uterine cervical distension.…”
Section: Introductionmentioning
confidence: 99%
“…The uterus and endocervix are innervated mainly by afferent fibers in the hypogastric nerve through which sensory information, including obstetric or gynecologic pain from distension, infection, or malignancy, is transmitted to the CNS (Berkley et al 1990;Peters et al 1987). Behavioral studies and clinical experience with paracervical blockade to provide pain relief in parturients and nonpregnant patients undergoing dilatation of the cervix indicates the hypogastric nerve is relevant to pain from this structure (Bonica 1994).…”
Section: Introductionmentioning
confidence: 99%